Multiscale modeling of Thermoelectric Generators for conversion performance enhancement. (February 2015) - Zhou, Siyi; Sammakia, Bahgat G.; White, Bruce; Borgesen, Peter; Chen, Cheng
Abstract: The thermoelectric model developed previously is used in this study to theoretically analyze promising solutions to enhance the power generated by Thermoelectric Generators (TEGs), which incorporate water-fed heat exchangers with commercially available thermoelectric modules. The patterned topography on wall surfaces is implemented and the increased device performance can be observed by introducing stirred flows into the heat exchangers and equalizing the temperature across the channels. Referring to the analysis, an approximately 30% enhancement in power generation is captured for the base-relief TEG, indicating it is desirable to have mixing structures. In addition, varying cross-sectional area of a single channel in a conversion capability sense shows that the structured surfaces have a stronger impact on the TEGs at the micro scale, which could promote the power output by 40%. Finally, the prospect of increasing the thermal transport capability of water by loading it with nanoparticles in the TEGs with macro and micro heat exchangers is explored. It is found that the conversion performance of the nanofluid-fed TEG only performs superior to the water-fed TEG at the micro scale by 14%, where the flow rate is relatively low. As for the macro scale, no improvement can be captured.